Extraperitoneal versus transperitoneal cesarean section: a retrospective study. Issue 1 (2nd January 2023) - Ji, Chao; Chen, Meng; Qin, Yichen
ABSTRACT: Objectives: To evaluate extraperitoneal cesarean section as a routine elective surgery. Methods: In this retrospective study, 461 primiparas were divided into the extraperitoneal and transperitoneal cesarean section groups according to the operation type in a random, but non-blinded, manner. The outcome measures were intraoperative blood loss, operation duration, postoperative gas passage time, postoperative pain, postoperative complications, and neonatal indicators Results: The operation duration of the extraperitoneal cesarean section group was significantly lower than that of the transperitoneal cesarean section group (P < 0.05). Compared to the transperitoneal cesarean section group, the extraperitoneal cesarean section group had neonates with higher birth weights and fewer neonatal transfers (P < 0.05). There was no difference in other maternal surgical or neonatal complications between the two groups. Conclusion: While extraperitoneal cesarean section can be safely performed as a routine procedure in the surgical delivery of primiparas, it must be performed by well-trained surgeons. In view of its advantages, it is worth being promoted in senior general hospitals as a routine choice. Abbreviations: CS: Cesarean section; ECS: Extraperitoneal; TCS: Transperitoneal; VAS: Visual analogue scale.